Peluang Peran Serta Para Ahli Hukum Islam di Indonesia dalam Perumusan Kebijakan Publik - Erik Darmawan (Jurnal Studi Sosial dan Politik, 2018)
Indonesia is a predominantly Muslim country. Muslims have their own rules of life, needs and interests that must be met that are different from other community groups. With its existence, the Indonesian Muslims are a group of interests. In the context of the life of the state, the needs and interests of Muslims can be fulfilled legally formal through their active participation in the political process and the process of public policy formulation. This paper examines the opportunities that Islamic jurists can take in the process of public policy formulation so that the needs and interests of Muslims can be met. The trick is to formulate new laws based on actual Islamic values, based on problems and realities in society and then propose them into a public policy. Islamic jurists must also actively engage in the process of public policy formulation. That is an opportunity that Muslim jurists can gain in helping people meet their distinctive needs and interests.